Power dependence of size of laser ablated colloidal silver nanoparticles - Talukder, A. I.; Sultana, Parvin; Haider, A F M Yusuf; Wahadoszamen, Md; Abedin, Kazi Monowar; Farhad, S.F.U. (© 2010 EDP Sciences, SIF, Springer-Verlag Berlin Heidelberg, 2017)
This article was published in the European Physical Journal D [© 2010 EDP Sciences, SIF, Springer-Verlag Berlin Heidelberg] and the definite version is available at : 10.1140/epjd/e2010-00204-7